Pengaruh Pemberian Sumber Silikon pada Sifat Kimia dan Pertumbuhan Tanaman Padi pada Tiga Jenis Tanah - Mirawanty Amin; Hartin Kasim; Faisal Faisal (Jurnal Ilmu Pertanian Indonesia, 2021)
Silicon (Si) has an important role in the growth of rice plants and some soil chemical properties. However, Si still receives less attention, because there is still little information about the importance of Si for rice plants and not many researches have been done on the use of Si in rice plants. This condition causes the farmers do not practice the use of Si as a fertilizer that eventually removal or release of silica from the soil solum. One source of Si that can be used as a fertilizer is trass. Currently, the trass has been widely used by the community as the basic material for making bricks. However, the use of trass as a source of Si in agriculture is not widely known. Therefore, it is necessary to evaluate the effect of trass on rice plant growth and soil chemical properties. The purpose of this study was to analyze the effect of trass addition on soil chemical properties and rice growth. The experimental design used was a separate plot where three types of soil, namely oxisol, inceptisol, and vertisol as the main plot and seven doses of trass were 0 (D0); 1.25 (D1); 2.5 (D2); 3.75 (D3); 5 (D4); 7.5 (D5); and 10 (D6) g kg-1 of soil as sub-plots. The treatment was a combination of these two factors and was repeated 3 times to obtain 63 experimental units. The results showed that the administration of trass significantly increased pH, available P, Ca-dd, Mg-dd, and significantly decreased available Fe and Mn. Meanwhile, the provision of trass also significantly affected plant height, namely 91 cm, and the number of tillers, namely 21 stems. Key words: chemical properties, rice, silicon, trass